Morfologia e anatomia foliar de espécies de angiospermas com ocorrência nos campos de areais do bioma pampa - Viana, Aline (2018)
(Morphology and foliar anatomy of angiosperm species occurring in the sand fields of the Pampa biome). Part of the vegetation in the southwest of Rio Grande do Sul (RS) is classified as sand fields, phytophysiognomy of the Pampa with sandy soils, susceptible to the natural process of sandstone, intensified by anthropic action. This process has contributed to a reduction in the biological diversity of the biome and is even more worrisome for species with restricted occurrence and/or the threat of extinction. The objective of this work was to characterize the leaf blade morphoanatomy of 20 angiosperm species of the sand fields, of which 8 are considered endangered, seeking to identify strategies that allow adaptation to the rural environment. To this end, individuals from different populations of each species were collected in sand-field regions of the Pampa biome. Leaf blades in frontal view were analyzed using scanning electron microscopy (SEM), light microscopy (LM), and transverse sections (TS) in LM. Microchemical tests were also performed in TS observed in LM. It was observed that, although they belong to distinct phylogenetic groups, many of the studied species share characteristics which can be interpreted as adaptive strategies, such as trichomes covering the entire leaf surface, stomata on both sides, compact mesophyll, druses, secretory channels, phenolic compounds, and mucilage. We conclude that these species, occurring in sand-field regions, have characteristics that confer adaptation to dry environments and/or water deficits. In this way, we emphasize the importance of the creation of conservation units in the sand-field region, aiming to preserve these species.